A comparative analysis of five commonly implemented declustering algorithms - Perry, Mason (2024)
Declustering of earthquake catalogs, that is determining dependent and independent events in an earthquake sequence, is a common feature of many seismological studies. While many different declustering algorithms exist, each has different performance and sensitivity characteristics. Here, we conduct a comparative analysis of the five most commonly used declustering algorithms: Garnder and Knopoff (1974), Uhrhammer (1986), Reasenberg (1985), Zhuang et al. (2002), and Zaliapin et al. (2008) in four different tectonic settings. Overall, we find that the Zaliapin et al. (2008) algorithm effectively removes aftershock sequences, while simultaneously retaining the most information (i.e. the most events) in the output catalog and only slightly modifying statistical characteristics (i.e. the Gutenberg Richter b-value). Both Gardner and Knopoff (1974) and Zhuang et al. (2002) also effectively remove aftershock sequences, though they remove significantly more events than the other algorithms. Uhrhammer (1986) also effectively removes aftershock sequences and removes fewer events than Gardner and Knopoff (1974) or Zhuang et al. (2002), except when large magnitude events are present. By contrast, Reasenberg (1985) only effectively removed aftershocks in one of the test regions.